The notion of “spetie humana” in the thought of Lucrezia Marinella - De Tommaso, Emilio Maria (Itinerari, 2023)
This paper focuses on one of the most original ideas in Lucrezia Marinella’s The Nobility and Excellence of Women (1600), that is the notion of ‘human species’. Traditionally, an ontologically strong concept of species operates in the philogynist literature of the Querelle des femmes, according to which men and women are considered as members of the same species because they share the same ontology, i.e., they have the same soul, and gender differences are seen as mere products of their corporeal constitution. Like many eminent defenders of women, including Baldassare Castiglione, Heinrich Cornelius Agrippa, Moderata Fonte, Maria Gondola, and Arcangela Tarabotti, Lucrezia Marinella apparently adopts this view, affirming that women are of the same species as men and have the same soul and the same powers. However, a careful analysis of her Nobility reveals that she proposes an ontologically weak idea of species, arguing that men and women do not share the same essence, because they have different souls, but they share secondary qualities, such as rationality and intellectual skills.